Study on the Pasture Establishment Technique Vii. Effectiveness of Mechanised Seed Drill for Establishment of Sewan Grass Lab/Urub S/Ndigus Pasture in Sandy Desert Soil - Chakravarty, A K; Verma, C M (Annals of Arid Zone, 2016)
An experiment with 2 methods of sowing (seeding by seed drills and seeding by hand in furrows opened by tractor drawn cultivator), 4 spacings (30 em. 60 em, 90 em and 120 em) and 2 seed treatments (pelleting and nonpelleting) was conducted in sandy soil of the Central Research Farm, Jodhpur. There was no significant difference in germination of Sewan grass (Lasiurus sindicus Henr) due to different methods of sowings and spacing but pelleted seeds resulted in comparatively poor germination (60-90 em) spacing between the rows indicated better growth of plants There was no significant difference in forage production in different cuttings due to different sowing methods and spacing treatments but non-pelleted seeds resulted in better stand and production compared with pelleted seeds.